Evaluation of seasonal variability in magnitude of urban heat islands using local climate zone classification and surface albedo - Dutta, K.; Basu, D.; Agrawal, S. (International journal of environmental science and technology (Tehran), 2022)
Surface Urban Heat Islands significantly deteriorate urban sustainability and livability. Effective ways to monitor and mitigate this phenomenon are gaining importance among environment researchers. In order to lessen the extreme heat waves of tropical cities, an understanding of the spatial features affecting urban micro-climate is needed. Local climate zones can provide the much needed framework for city level climate studies. This paper presented satellite imagery-based workflow to identify critical zones within a city, using the spatial thermal characteristics. The results brought out the critical thermal scenario in summer, for two mega cities of India. Prolonged heat trapping resulted in 13.99% nocturnal heat island cover in the New Delhi region and 22.26% in the Kolkata City region. Moderate to strong heat stress was observed for central city areas, even at night time. Surface temperature variation within local climate zones of a city reflected significant rise in temperature over certain urban pockets due to building morphology. Over a distance of 12 km from vegetated land to low-rise dense built-up, a drastic 8.76 °C temperature rise was noted on a summer night. The temperature patterns were further verified with seasonal surface albedo mapping. Based on areal distribution, location, thermal range and contribution in heat island formation, sustainable planning strategies for each local climate zone were laid out. The study aimed to achieve an optimum cooling level for given urban structures and also highlighted the potential thermal environment changes faced by suburban regions.